Wild LA : explore the amazing nature in and around Los Angeles - Higgins, Lila M.; Pauly, Gregory B.; Goldman, Jason G.; Hood, Charles, 1959- (Timber Press ; Natural History Museum of Los Angeles County, 2019)
"A dynamic, fact-filled guide to the natural world of Los Angeles from the experts at the Natural History Museum"--